2017
DOI: 10.3390/genes8100256
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Pericentral Retinitis Pigmentosa—A Form of Mild Retinitis Pigmentosa

Abstract: Pericentral retinitis pigmentosa (RP) is an atypical form of RP that affects the near-peripheral retina first and tends to spare the far periphery. This study was performed to further define the genetic basis of this phenotype. We identified a cohort of 43 probands with pericentral RP based on a comprehensive analysis of their retinal phenotype. Genetic analyses of DNA samples from these patients were performed using panel-based next-generation sequencing, copy number variations, and whole exome sequencing (WE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 50 publications
10
32
0
Order By: Relevance
“…Consistent with previous reports [21], we found that pericentral RP is a rather uncommon RP subtype and has extensive genetic heterogeneity. Genetic defects underlying pericentral RP are overall overlapping those causing mild forms of typical RP, as previously suggested [4]. While previous studies [3][4][5] found pericentral RP cases almost exclusively in the context of non-syndromic forms, we observed a high prevalence of pericentral RP within the syndromic RP group, mainly in Usher syndrome.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Consistent with previous reports [21], we found that pericentral RP is a rather uncommon RP subtype and has extensive genetic heterogeneity. Genetic defects underlying pericentral RP are overall overlapping those causing mild forms of typical RP, as previously suggested [4]. While previous studies [3][4][5] found pericentral RP cases almost exclusively in the context of non-syndromic forms, we observed a high prevalence of pericentral RP within the syndromic RP group, mainly in Usher syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…Genetic defects underlying pericentral RP are overall overlapping those causing mild forms of typical RP, as previously suggested [4]. While previous studies [3][4][5] found pericentral RP cases almost exclusively in the context of non-syndromic forms, we observed a high prevalence of pericentral RP within the syndromic RP group, mainly in Usher syndrome. In agreement, variants in USH2A were detected in over 40% of the solved cases in our cohort.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The variants that were pathogenic by the functional assay were not uniformly predicted to be damaging based on computational predictions alone ( Table 2). Both of the subjects with the G18D mutation and the one subject with the G101V mutation had a phenotype of pericentral retinitis pigmentosa, as described in further detail (Comander, 2017).…”
Section: Probands With a Rare Rho Vusmentioning
confidence: 88%